Optimization of third-order trajectory to reduce the vibration in a point-to-point motion system - Tatte, Rupesh; Jawale, Hemant; Thorat, Hemant (Vietnam Journal of Science and Technology, 2025)
In point-to-point motion transfer applications, where motion is executed from one point to another along a pre-planned path with high speed and precision, the occurrence of vibration is a common problem. This problem is addressed through motion profile planning, where an S-curve motion profile is reported to produce lesser vibration than a trapezoidal velocity profile. This paper introduces an optimization method designed to optimize a polynomial-function-based 7-segment third-order symmetrical (7-STOS) S-curve motion profile to minimize vibration. The method aims to achieve lower vibration amplitude for a given distance travelled and motion time (MT) without considering the dynamics of the system. The optimization method is developed using a novel unitization and the weighted sum method. The effectiveness of the proposed method is demonstrated using an experimental setup of a flexible rotating link. The modelling of flexible rotating links is provided to facilitate the validation of experimental results with simulated results.